2022
DOI: 10.3390/biomedicines10061391
|View full text |Cite
|
Sign up to set email alerts
|

Role and Function of Mesenchymal Stem Cells on Fibroblast in Cutaneous Wound Healing

Abstract: Skin wounds often repair themselves completely over time; however, this is true only for healthy individuals. Although various studies are being conducted to improve wound-healing therapy outcomes, the mechanisms of wound healing and regeneration are not completely understood yet. In recent years, mesenchymal stem cells (MSCs) have been reported to contribute significantly to wound healing and regeneration. Understanding the function of MSCs will help to elucidate the fundamentals of wound healing. MSCs are mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 134 publications
1
5
0
Order By: Relevance
“…Very similar results were published by Pommato et al, where EVs of AT-MSCs and BM-MSCs were used to study beneficial effects on the proliferation capacity and migration of fibroblasts, keratinocytes, and endothelial cells [14]. The mechanism of this activity could be explained by the release of growth factors such as EGF, bFGF, and TGF that increase the proliferation and migration of fibroblasts [35,36]. Very similar results were published by Liu et al from their study focused on the migration and activation of human skin fibroblasts affected by MSC conditioned medium [37].…”
Section: Discussionsupporting
confidence: 63%
“…Very similar results were published by Pommato et al, where EVs of AT-MSCs and BM-MSCs were used to study beneficial effects on the proliferation capacity and migration of fibroblasts, keratinocytes, and endothelial cells [14]. The mechanism of this activity could be explained by the release of growth factors such as EGF, bFGF, and TGF that increase the proliferation and migration of fibroblasts [35,36]. Very similar results were published by Liu et al from their study focused on the migration and activation of human skin fibroblasts affected by MSC conditioned medium [37].…”
Section: Discussionsupporting
confidence: 63%
“…In (dermal) wound healing processes, for example, recruited (and activated) MSCs ‘animate’ fibroblasts to produce the appropriate amounts of collagen fibers needed for tissue repair. MSC-secreted factors at the same time prevent scar formation and limit inflammation, fostering a return to a normal healthy state ( 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that proliferating and actively synthesizing cells of the transplant significantly reduce the concentration of reactive oxygen species through the synthesis of antioxidant defense enzymes (Jena et al, 2023;Chettouh-Hammas et al, 2023). In a series of studies, it has been demonstrated that culturing keratinocytes under unfavorable conditions without the support of fibroblasts or mesenchymal cells leads to the complete death of keratinocytes through apoptosis after 14 days of cultivation (Tanaka et al, 2022, Xu et al, 2023. However, when keratinocytes are cultured on a collagen gel with fibroblasts, they do not undergo apoptosis and actively proliferate (Tahri et al, 2023;Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%